ASSESSMENT, MONITORING AND PROTECTION OF GROUNDWATER POLLUTION IN URBAN AREAS - CORDOBA CITY - ARGENTINA - Ferral Anabella; Sarmiento Tagle Martin; Alaniz Eugenia; Ferral Alberto (European Scientific Journal, ESJ, 2014)
Urbanization increases the impervious surfaces. These impervious surfaces result in increased storm-water runoff, which consequently carries with it any dirt, chemicals, or pollutants which have been dripped, spilled, or leaked into these surfaces. Whether the runoff eventually percolates into the ground or enters a nearby stream or Wadi, the carried pollutants will eventually reach and contaminate the groundwater. On the other hand, activities such as improper waste disposal and neglected cesspits can also contaminate the watershed groundwater resources. The main objective of this research is to develop guidelines for governments, water managers, spatial planners and environmental managers in order to understand the impacts of polluting activities on groundwater resources in urban catchments and use them in order to develop strategies for groundwater protection. Aquifer under Cordoba City consists of Quaternary sediments with moderate hydraulic conductivity. Groundwater chemistry shows high concentrations of Sulphate and Chloride. In some industrial areas, concentrations of Nitrates, Arsenic, Fluorine and Bacteria Coliformes exceed tolerable limits. Major sources of pollution are urban wastewater, urban storm water, solid waste disposal sites. Analysis shows that urban storm waters consist of very high concentrations of TSS, BOD, COD, N-NH4+, N-NO3-, and PO4. The vulnerability map of Cordoba city shows zones of moderate and high vulnerability. The DRASTIC index has values ranging from 101 to 193. Aware of the need to more extensive knowledge for the protection of the groundwater resource, a hydro geological modeling of the phreatic aquifer was made by means of the MODFLOW code in order to study the dynamics of the groundwater system and have a tool for future predictions.